New Media Dramaturgy - Eckersall, Peter. author. aut Link
XI, 236 p. 22 illus.
Keywords: This book illuminates the shift in approaches to the uses of theatre and performance technology in the past twenty-five years and develops an account of new media dramaturgy (NMD), an approach to theatre informed by what the technology itself seems to want to say. Born of the synthesis of new media and new dramaturgy, NMD is practiced and performed in the work of a range of important artists from dumb type and their 1989 analog-industrial machine performance pH, to more recent examples from the work of Kris Verdonck and his A Two Dogs Company. Engaging with works from a range of artists and companies including: Blast Theory, Olafur Eliasson, Nakaya Fujiko and Janet Cardiff, we see a range of extruded performative technologies operating overtly on, with and against human bodies alongside more subtle dispersed, interactive and experiential media.